Transversus abdominis plane block in urological procedures: A systematic review and meta-analysis. Issue 7 (July 2021) - Zayed, Mohamed; Allers, Katharina; Hoffmann, Falk; Bantel, Carsten
Abstract : BACKGROUND: Transversus abdominis plane (TAP) blocks have been shown to successfully reduce pain and opioid consumption after general and gynaecological surgery. OBJECTIVE: To evaluate whether TAP blocks alleviate pain and opioid consumption after urological procedures. DESIGN: A systematic review and meta-analysis. DATA SOURCES: MEDLINE, Embase and CENTRAL. ELIGIBILITY CRITERIA: Without language restriction, randomised controlled trials (RCTs) that compared the effects of TAP blocks with placebo or no treatment in urological surgery. MAIN OUTCOME MEASURES: Primary outcomes were pain intensities at rest and movement at 6, 12 and 24 h after surgery. Secondary outcomes were postoperative opioid consumption in the first 24 h after surgery and postoperative nausea and vomiting. We performed meta-analyses using random effects models. Effect sizes were expressed as mean differences for continuous variables. We used the Cochrane risk of bias tool (RoB 2.0) to assess risk of bias. RESULTS: We analysed 20 RCTs comprising a total of 1239 patients. The risk of bias of the studies was relatively high. TAP blocks significantly reduced postoperative pain at all time points compared with placebo or no treatment. Mean differences on an 11-point pain intensity scale were between 0.55 (95% CI: −0.90, to −0.21; P  = 0.002; I 2  = 94%) to 1.13 (95% CI: −1.62 to −0.65; P  < 0.001; I 2  = 95%) less at rest and 0.74 (95% CI: −1.25 to −0.23; P  = 0.005; I 2  = 79%) to 1.32 (95% CI: −1.83 to −0.81; P  < 0.001; I 2  = 68%) less on movements. TAP blocks also reduced opioid consumption in the first 24 h after surgery significantly by 12.25 mg (95% CI: −17.99 to −6.52 mg; P  < 0.001; I 2  = 99%) morphine equivalents. Possibly, this had no influence on postoperative nausea and vomiting (risk ratio: 0.98; 95% CI: 0.66 to 1.45; P  = 0.91; I 2  = 30%). CONCLUSION: TAP blocks seem to offer improved analgesia when used after urological surgery. However, due to the large heterogeneity between and the considerable risk of bias within the included studies results should be viewed with caution. SYSTEMIC REVIEW REGISTRATION: PROSPERO CRD42018112737. Abstract : Supplemental Digital Content is available in the text